RANCANG BANGUN POINT OF SALES TERINTEGRASI DENGAN SISTEM GUDANG - Mohamad Jamiludin; Choirul Anam; Agus Sifaunajah (KH. A. Wahab Hasbullah University, 2019)
The main purpose of establishing an information system is to facilitate human work easier. In this study, the Point of Sales (POS) information system is a system that regulates the flow and also the sale and purchase reports or transactions as well as incoming goods from the production process. The latest goal is that the system can provide valid reports, both transaction reports and goods reports. Therefore the author develops a system that has been running at PT. MAAN GHODAQO SHIDDIQ LESTARI which still uses a Microsoft Excel based on the system. Where the system is still using manual methods in processing transaction data and incoming goods. In the development of this application, the author uses the UML modelling language (Unified Modeling Language). While in the implementation stage the author uses the PHP programming language for servers and warehouse administrators and uses Basic4android programming language for sales. The result of the development of the system is an integrated POS information system, in that integration is expected to be able to regulate sales transactions and also incoming goods from the production process. Keywords: point of sales, unified modelling language, PHP, basic4android